An Assessment of Usual Salt Intake among Older Normotensive Adults in Atonsu, a Suburb of Kumasi in the Ashanti Region of Ghana - Rufai Safianu; Jacob Plange-Rhule (International Journal of Hypertension)
Background. Globally, sodium intake has been found to be far above the normal level required by the body. Within countries, variations in salt intake exist between rural communities and urban communities. Experimental and epidemiological studies as well as studies involving clinical trials show the existence of adverse effect of salt consumption on the blood pressure of adults. The study evaluated salt intake among older normotensive adults in Atonsu, a suburb of Kumasi in the Ashanti region of Ghana. Methods. Participants were randomly selected from five churches which constituted cluster samples. A questionnaire was administered to participants for demographic information and dietary and lifestyle assessments. The study targeted 100 participants, twenty from each of the five churches. Eighty-two individuals gave their informed consent. Out of the 82 who gave their informed consent, 15 withdrew and 67 completed the course. The 67 participants comprised 36 (53.7%) men and 31 (46.3%) women. Systolic and diastolic blood pressure, BMI, urinary sodium, urinary potassium, serum creatinine, serum sodium, and serum potassium concentrations were also measured. Results. Participants’ mean age was 52.3 ± 8.7 years. Participants had 24 hr urinary sodium excretion of 153.0 ± 26.9 mmol/day. All participants indicated that they consume foods high in salt even though none of them added salt to their diet at table. Mean 24 hr urinary potassium was 52.5 ± 12.9 mmol/day. Mean systolic blood pressure was 119.9 ± 10.8 mmHg and mean diastolic blood pressure was 72.5 ± 7.3 mmHg. Their mean BMI was 23.7 ± 3.5 kg/m2. Conclusion. The participants who can be described as quite old and normotensive were high salt consumers, indicated by their dietary assessment and urinary sodium excretion, even though they had normal blood pressure.